2013
DOI: 10.1016/j.rppneu.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do equilíbrio entre oxidantes e antioxidantes na patogénese da doença pulmonar obstrutiva crónica

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is one of the most common chronic diseases and a major cause of morbility and mortality. An imbalance between oxidants and antioxidants (oxidative stress) has been proposed as a critical event in the pathogenesis of COPD. The increased oxidative stress in patients with COPD is the result of exogenous oxidants namely pollutants and cigarette smoke as well as endogenous oxidant production during inflammation. The aim of the present study was to clarify the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Likewise, increased peroxidation of lipids and oxidation of proteins of the erythrocytes and platelets from patients with COPD and asthma were confirmed by de Castro et al [28]. A higher concentration of MDA in the blood plasma of COPD patients, as compared with that found in healthy subjects, was found by Cristóvão et al [29]. Folchini et al [30] observed statistically significant differences between the blood TBARS levels in patients with COPD depending on the gravity of the disease.…”
Section: Discussionmentioning
confidence: 70%
“…Likewise, increased peroxidation of lipids and oxidation of proteins of the erythrocytes and platelets from patients with COPD and asthma were confirmed by de Castro et al [28]. A higher concentration of MDA in the blood plasma of COPD patients, as compared with that found in healthy subjects, was found by Cristóvão et al [29]. Folchini et al [30] observed statistically significant differences between the blood TBARS levels in patients with COPD depending on the gravity of the disease.…”
Section: Discussionmentioning
confidence: 70%
“…A significant decrease in non-protein SH groups, mainly in the form of reduced GSH, has been found in many of the examined studies [28, 34, 40, 41, 43, 45, 53] (Table 1). No differences have been found considering only mild COPD [55] (Table 1).…”
Section: Introductionmentioning
confidence: 76%
“…A decreased level of vitamin C [25, 28, 62] and E [25, 28, 30], as well as no difference in the levels of vitamin A [27], C [40, 48, 95] and E [27] has been described in COPD compared to healthy controls. No differences have also been found in the different stages of severity of disease [96].…”
Section: Introductionmentioning
confidence: 99%
“…If inflammatory cytokines are produced chronically, then c-Abl will remain activated, and primed tissue neutrophils will continue to produce ROS. This appears to be a major contributor to tissue damage resulting from inflammatory disease, including chronic obstructive pulmonary disease (COPD) [7-10]. COPD is the sixth largest cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%